Preparation and Evaluation of Aegle marmelos Gum as Tablet Binder - Patil D.N; Kulkarni A.R; Hatapakki B.C; Patil B.S (International Journal of Pharma and Bio Sciences, 2010)
In the present work, we have formulated the oral tablets of paracetamol by using Aegle marmelos fruit gum as a binder. The four different tablet formulations were prepared by wet granulation method. The binder concentrations used in the formulation were 2, 4, 6 & 8 % w/w of cordia fruit gum; tablets were subjected for evaluation of hardness, friability, drug content uniformity. Preliminary evaluation of granules showed that, 0.71 to 0.77 mm granule size, 29.20 to 30.10º angles of repose and 22.1 to 12.7 % fines. Hardness was found to be in the range of 7.1 to 7.4 kg/cm2, the percent friability was in the range of 1.50 to 0.75 %, and tablet showed 97.46 to 98.96 % of labeled amount of paracetamol indicating uniformity in drug content, 8 to 18 min disintegration time and more than 90% dissolution in 75 min. Tablets at 6 % w/w binder concentration showed more optimum results as tablet binder. The Aegle marmelos gum was found to be useful for the preparation of uncoated tablet dosage form.